Effects of starvation on muscle and organ mass of King Eiders Somateria spectabilis and the ecological and management implications - Fournier, Michael A; Hines, James E (Wildfowl, 2025)
In the spring of 1990 we salvaged 21 carcasses of starved King Eiders from the Tuktoyaktuk and McKinley Bay areas of the Northwest Territories. The carcasses were dissected and muscle and organ mass were measured for comparison with shot birds obtained from the Inuit hunters of Homan, N.W.T. Most muscles and organs were significantly smaller in starved birds. The exception was the gizzard which was larger in starved birds. Average mass loss at death was approximately 45% of estimated initial body mass in males and 53% in females. This was reflected in the percent mass loss of individual muscles and organs. Starved females lost an estimated 4% more supracoracoideus mass, 4% more pectoralis mass, 5% more heart mass, 4% more gonad mass, 4% more liver mass, and 8% more intestine length than starved males when compared to their shot counterparts. The amounts and types of materials found in the gizzards of starved eiders varied considerably from that found in the gizzards of shot birds. Periods of starvation, either lethal or sublethal, during spring migration may have a severe impact on King Eider population dynamics.